0958 Sleep and Inflammatory Profiles in Bipolar Disorder. (27th April 2018) - Kaufmann, C N; Sutherland, A; Nakhla, M Z; Yoon, H; Soontornniyomkij, B; Eyler, L T
Abstract: Introduction: There is evidence for accelerated aging in bipolar disorder, perhaps due to irregularities in inflammatory profiles. One mechanism may be sleep disturbances, which are common in bipolar disorder and associated with inflammation. This study examined the association between objectively measured sleep quality and levels of inflammatory cytokines of IL-6, TNF-alpha and CRP. Methods: Data came from an ongoing study investigating cognitive and biological aging in bipolar disorder, and included 57 subjects (17 with bipolar disorder [BD] and 40 healthy comparison [HC] subjects) who had complete data for inflammatory assays and wrist actigraphy. Subjects completed wrist actigraphy for two weeks and had three blood draws spaced evenly over that period. We compared blood levels of IL-6, TNF-alpha, and CRP (averaged across the three blood draws) between BD and HC groups, and assessed their association with sleep indices (total sleep time [TST], wake after sleep onset [WASO], sleep onset latency [SOL], and sleep efficiency [SE]) across the two-week period. Inflammatory measures were log-transformed. Results: Compared to HCs, BD subjects slept an average of 1-hour less (t(55) =3.03, p=0.004), had more variable sleep efficiency (t(55) =-2.78, p=0.008), had higher levels of IL-6 (t(55) =-3.33, p=0.002) and TNF-alpha (t(55) =-4.19, p<0.001), and marginally higher levels of CRP (t(55) =-1.76, p=0.084). In the combined sample, greater mean TST and SE was associated with lower IL-6 (TST: r=-0.35, p=0.007; SE: r=-0.29, p=0.028). Greater variability in SE was associated with higher IL-6 (r=0.30, p=0.025). Among HCs, greater mean SE was associated with lower IL-6 (r=-0.33, p=0.038). In BDs, there were moderate effect sizes for relationships between mean TST with TNF-alpha, and SOL and SE variability with IL-6, but these were not statistically significant. There were no interactions by diagnostic groups. Conclusion: BD subjects had abnormal sleep indices and greater inflammation. While TST and SE were associated with IL-6 in combined sample, the association between inflammation and sleep quality did not differ by diagnosis groups. Night-to-night mechanisms for inflammatory differences will be explored. Support (If Any): National Institute of Mental Health (R01MH103318 and T32MH019934).